Aspect Analysis of Data Systematization of Library’s Document Collection, and Scientific Landscape - A. N. Sysoev; V. N. Beloozerov (Informaciâ i Innovacii)
The paper discusses the method of aspect analysis of classification indexes of the document collection of libraries. The method allows you to establish links between the Sciences and information flows between them, which determines the landscape of scientific knowledge. The object of analysis is a set of composite classification indexes containing pointers to relevant areas of knowledge as aspects. The proposed approach can be used in scientometric research.